2007
DOI: 10.1007/s10877-007-9101-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Clinical Application of a First Order Step Response Equation for Nitrogen Clearance During FRC Measurement

Abstract: ObjectiveTo derive a difference equation based on mass conservation and on alveolar tidal volumes for the calculation of Functional Residual Capacity. Derive an equation for the FRC from the difference equation. Furthermore, to derive and validate a step response equation as a solution of the difference equation within the framework of digital signal processing where the FRC is known a priori.MethodsA difference equation for the calculation of Functional Residual Capacity is derived and solved as step response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The current EELV measurement technique (F IO 2 stepchange then nitrogen washout) was pioneered by Stenqvist and colleagues, 41,42 and several early studies with lung models, animals, and patients found the method accurate and reproducible. [42][43][44] However, the evidence regarding the value of EELV in critically ill patients remains sparse. Bikker et al recently compared EELV in mechanically ventilated patients to reference equations for FRC.…”
Section: Accuracy and Applicationmentioning
confidence: 99%
“…The current EELV measurement technique (F IO 2 stepchange then nitrogen washout) was pioneered by Stenqvist and colleagues, 41,42 and several early studies with lung models, animals, and patients found the method accurate and reproducible. [42][43][44] However, the evidence regarding the value of EELV in critically ill patients remains sparse. Bikker et al recently compared EELV in mechanically ventilated patients to reference equations for FRC.…”
Section: Accuracy and Applicationmentioning
confidence: 99%
“…The derivation of the modified washin/washout method for adult patients was detailed in Olegard et al 13 and Choncholas et al 14 Carbon dioxide production () was obtained from the gas analyzer of the monitor (COMVX, S/5, GE Health Care, Helsinki, Finland). The inspiratory minute ventilation () was calculated by Haldane transformation from the measured expiratory minute ventilation ().…”
Section: Methodsmentioning
confidence: 99%
“…These requirements preclude the use of this approach in pediatric settings. We introduced a multiple breath nitrogen washin/washout (MBNW) method, 13,14 modified from the original method by Darling 15 …”
mentioning
confidence: 99%
“…Despite numerous studies dealing with the methodological and technical aspects of FRC measurements in ventilated adult patients, 10,36,56,58,66–68,70–75,83–85 only a few studies have used FRC measurements during the treatment of patients.…”
Section: Clinical Applicationsmentioning
confidence: 99%